Dynamics and Effectiveness of SHGs in Chhattisgarh - Banshi Lal Sahu and Souvik Ghosh, (Indian Journal of Extension Education, 2016)
The present study was conducted in randomly selected Kanker district of Chhattisgarh. A random sample of total 12SHGs, three SHGs from each of four schemes viz. NABARD's SHG-Bank Linkage Programme (SBLP), National RuralLivelihood Mission (NRLM), Integrated Watershed Management Programme (IWMP), Agricultural TechnologyManagement Agency (ATMA), were selected. From each of 12 SHGs a sample of 10 members were chosen asrespondents in present study. The overall dynamics of SHGs studied based on 10 different indicators showed that fundgeneration, participation and norms were three most effective indicators while decision making, membership feeling andgroup atmosphere were relatively less effective. Overall, the dynamics of SHGs was not much varied (overall scoreranged from 72.90 to 75.43). SHGs under ATMA showed relatively lesser values for most of the indicators resultingrelatively low dynamics as compared to the SHGs under NABARD's SBLP, NRLM and IWMP. There were no significantdifferences between perceptions of members of SHGs formed under four different programmes with respect to self-help2group dynamics as evident from t-tests. Chi-square (x ) test of independence also showed the dynamics of SHGsperceived by the members was independent of their SHGs formed under different programmes. Age, caste, economicstatus and family land holding were significantly and negatively correlated with dynamics of SHGs. On the other hand,use of personal localite communication sources, use of mass media sources, communication/ information use pattern andsatisfaction of SHG member being part of her/ his SHG were significantly and positively correlated with dynamics ofSHGs. In the step-wise regression analyses, eight variables pertaining to characteristics of SHG members viz. use ofpersonal localite communication source, economic status, age, sex, satisfaction of member being part of her/ his SHG, useof mass media communication source, caste, and family land holding, together explained about 73 per cent variations(R2= 0.728) in dynamics of SHG.